Household economic resilience to catastrophic rainstorms and flooding in a Chinese megacity. (8th April 2016) - Lo, Alex Y.; Xu, Bixia; Chan, Faith; Su, Ruixian
Abstract: Megacities situated on flood plains face escalating risks of waterlogging and inundation. Tianjin is one of these megacities in China where residents are exposed to these risks and not well prepared for their consequences. Government policies should support the most vulnerable and less resilient groups. This study can inform policy‐making by identifying the socio‐economic characteristics of those who are financially better prepared for the consequences of catastrophic rainstorms and flooding. A structured questionnaire survey was administered to 332 Tianjin residents. Results confirm that financial conditions crucially determine household resilience to these natural hazards. Lower‐income and less educated urban residents have lower resilient capacity. Weak engagement in the community, including residential committees and other organisations, is related to lower capacity to cope with the economic consequences of extreme weather events. Less resilient groups are therefore those who are subject to urban poverty and have limited social capital. Tianjin and other cities in the developing world require resilience strategies that attend to this segment of urban population.